Exploring the impact of burnout on academic and athletic performance among women's varsity players - Tañada, Rachel Claire D. 2001-
At a university in Quezon City, this mixed-method study looked at how burnout affected women's varsity players' academic and athletic performance. Raedeke (1997) defines burnout as emotional or physical exhaustion, performance decrement, and devaluation of sport, therefore influencing a person's drive and performance level. Using convenience sampling—a non-random selection method based on availability and accessibility—seven players from a women's badminton team were selected. Focused group discussion and the Athlete Burnout Questionnaire (ABQ) helped collect the data. Contributing elements were inadequate recovery, too much training, academic pressure, and a negative training environment. Participants reported poor performance in both academic and athletic aspects, lower drive, and trouble with time management. Still, some teachers challenged these claims since students showed different degrees of performance in different courses. Essential components that greatly help to reduce burnout include recovery systems, support networks, and periodized training. Advice for coaches underlines the need to give training schedules top priority, improving communication, and encouraging player autonomy priority. Said to be necessary is parental support and possible access to sports psychologists. These elements taken together improve performance and help student-athletes have good mental health.